Is There a Gap in the Gap? Regional Differences in the Gender Pay Gap. (4th August 2013) - Hirsch, Boris; König, Marion; Möller, Joachim
Abstract: In this paper, we investigate regional differences in the gender pay gap both theoretically and empirically. Within a spatial model of monopsonistic competition, we show that more densely populated labour markets are more competitive and constrain employers' ability to discriminate against women. Utilizing a large administrative data set for western Germany and a flexible semi‐parametric propensity score matching approach, we find that the unexplained gender pay gap for young workers is substantially lower in large metropolitan than in rural areas. This regional gap in the gap of roughly 10 percentage points remained surprisingly constant over the entire observation period of 30 years.